Moving forwards: A problem for full ectogenesis. (15th February 2021) - Baron, Teresa
ABSTRACT: Most existing literature on the ethics of full ectogenesis has proceeded under the presupposition that science will at some point produce sophisticated technologies for full‐term gestation (from embryo to infant) outside the human womb, delivering neonate health outcomes comparable with (or even superior to) biological gestation. However, the development of this technology—as opposed to the support systems currently being advanced—would require human subject experiments in embryo‐onwards development using ectogenic prototypes. Literature on ectogenic research ethics has so far focused on 'backwards' development of partial ectogenesis: incubation and ectogestation technologies that would allow the support of earlier and earlier neonates and foetuses. However, little has been said about the ethics of 'forwards' development of (partial or full) ectogenesis, involving the development of embryos and foetuses in prototype environments. Such a prototype might allow us to produce a gestateling or live neonate from a human embryo, but with poorer expected development and health outcomes than from biological gestation; it might also produce only gestatelings (healthy or otherwise) before the technology was developed to a stage where full‐term gestation was achievable. This paper explicates some of the ethical issues that this raises for the development of 'full' ectogenesis, and presents prima facie reasons to consider this research problematic and therefore to require extensive further argument in its defence.